2015
DOI: 10.1007/s10067-015-2907-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel markers of endothelial dysfunction and inflammation in Behçet’s disease patients with ocular involvement: epicardial fat thickness, carotid intima media thickness, serum ADMA level, and neutrophil-to-lymphocyte ratio

Abstract: The etiology of Behçet's disease (BD) has not been fully elucidated. However, immunological and environmental factors, endothelial dysfunction (ED), and genetic susceptibility have been proposed to play a role. In this study, we aimed to evaluate epicardial fat thickness (EFT) together with serum asymmetric dimethylarginine (ADMA), carotid intima media thickness (CIMT), and neutrophil-to-lymphocyte ratio (NLR) in BD patients with ocular involvement. Thirty-six ocular BD patients (17 active and 19 inactive ocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 37 publications
0
23
0
3
Order By: Relevance
“…In recent years, neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) have received attention as potential new markers of systemic inflammation. In previous studies, NLR and PLR have been reported to be useful in systemic inflammatory diseases such as aortitis syndrome [6], Behçet's disease [7], Kawasaki disease [8], Henoch-Schönlein purpura [9], systemic lupus erythematosus [10], and anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) [11,12]. Furthermore, NLR and PLR have been proposed as markers of inflammation in patients with ESRD [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) have received attention as potential new markers of systemic inflammation. In previous studies, NLR and PLR have been reported to be useful in systemic inflammatory diseases such as aortitis syndrome [6], Behçet's disease [7], Kawasaki disease [8], Henoch-Schönlein purpura [9], systemic lupus erythematosus [10], and anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) [11,12]. Furthermore, NLR and PLR have been proposed as markers of inflammation in patients with ESRD [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Behçet’s disease can be classified as active and inactive diseases based on disease activity, and thrombosis occurs often in BD. Studies on MPV, NLR, and PLR in patients with BD in comparison with those in healthy controls, on the indices between active and inactive diseases, and between BD with and without thrombosis have reported controversial results . We performed the present meta‐analysis to overcome the limitations of individual studies and resolve inconsistencies .…”
Section: Introductionmentioning
confidence: 99%
“…NLR is a novel simple and inexpensive index for assessing inflammation [3]. Emerging evidence suggested that increased NLR was a potential marker of poor prognosis in multiple tumors [46] and cardiovascular diseases [79] in general population.…”
Section: Introductionmentioning
confidence: 99%